The impact of non-compliance with accounting standards on the quality of financial reporting - Ntuli, Linient (Midlands State University, 2017)
Issues of overnight corporate shut downs have raised some eyebrows. The trust that investors and other stakeholders had in the company executives, independent auditing firms, board of directors, financial analysts and information distributors (Corporate Reporting Supply Chain) is slowly fading away. Mitigation procedures have been dreamt of and conceived but most of them could not be birthed. This research then serves as an evaluation of the impact of non compliance to IFRSs/IASs on the quality financial statements in Zimbabwe. Through questionnaires and interviews to auditors, investment analyst, accounting educators and accountants of the companies listed on the Zimbabwe Stock Exchange, it came to light that listed companies are not yet in full compliance with IFRS disclosure requirements despite the threat of being delisted from the stock exchange. This has resulted in the financial statements failing to represent faithfully the economic phenomena they purport to represent thus not achieving their purpose of providing useful information that enables the users to make informed decisions.